Implementation of the Critical Path Method (CPM) in Web Applications for Project Scheduling with Python Programming - Meliska Eviany Raranta; Fabian J Manoppo; Grace Yoyce Malingkas (Journal of Social Research, 2025)
The construction industry faces complex challenges involving multiple phases, numerous stakeholders, and intricate interdependencies among activities. The Critical Path Method (CPM) is a proven technique for planning, organizing, and monitoring digital project scheduling activities. This research aims to develop a web-based application that implements CPM for project scheduling using the Python programming language. The study utilizes data from the Pancang Tiowor project by PT. Natural Indococonut Organik, with a contract value of Rp 5,145,000,000.00 and a 90-day execution period in 2024. The methodology comprises a literature review, requirements analysis, and CPM algorithm implementation, all integrated with an interactive interface built using the Streamlit framework. The application automatically computes Early Start (ES), Early Finish (EF), Late Start (LS), Late Finish (LF), and Slack values, while also providing network diagram visualizations. Validation results indicate that the web application delivers accurate calculations, consistent with both manual computations and Microsoft Project outputs. The identified critical path duration is 73 days, compared to the planned 90-day project duration, which provides a 17-day buffer for non-critical tasks. The application effectively offers an efficient, accessible, and user-friendly solution for digital project scheduling management.